If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(2+1)=11x-3
We move all terms to the left:
7(2+1)-(11x-3)=0
We add all the numbers together, and all the variables
-(11x-3)+73=0
We get rid of parentheses
-11x+3+73=0
We add all the numbers together, and all the variables
-11x+76=0
We move all terms containing x to the left, all other terms to the right
-11x=-76
x=-76/-11
x=6+10/11
| -x-42=5x | | 9h-15=9-3 | | 3x=+75 | | 10z-15=5z | | 5y+8=32-3y | | -8p+7+9p=14 | | 9r+5=5r+49 | | 5-7x=94 | | 2y+2y=180 | | 8x-3x-24=x+36 | | 4y-8=55-3y | | -6x+3=212 | | 4b+8=3b+17 | | 16=8^x-2 | | 8+9a=3a+10+6a | | 50-3t=4t-37 | | 32x+260=38x | | 5=4-y | | w(-8)=-21 | | 2t-18=22-3t | | 3x+9=-12+3x | | 13n+5=4n+41 | | X=x(2-×) | | 2w=23 | | 8/1+c=5/4 | | -2-5(2+5x)=30.5 | | x-7.53=9.95 | | −3.6−1.9t+1.2+5.1t=0 | | 2z-5(z+2)=-8 | | 6x/3+x=4x^2 | | 2/x^2=4/8 | | 24x^2-10x-4=0 |